2019
DOI: 10.1186/s12889-019-7208-0
|View full text |Cite
|
Sign up to set email alerts
|

Stunting, food security, markets and food policy in Rwanda

Abstract: Background Over the past two decades, Rwanda has experienced impressive economic growth, resulting in considerable improvements in living standards and poverty reduction. Despite these gains, progress on reducing the level of stunting in smallholder rural children, particularly boys, continues to be a serious concern. Methods Policies, dietary diversity and socio-economic factors that may influence stunting in rural Rwandan children were evaluated using a logit model wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 43 publications
(74 reference statements)
2
40
2
1
Order By: Relevance
“…Similarly, Huang and Tian [136] argue that enhanced accessibility to food, thanks to the development of market, has improved dietary quality among Chinese people and note that "the impact of food accessibility on dietary quality is stronger for those not engaged in agriculture production" (p. 92). Weatherspoon et al [137] investigate the linkages between food policy, markets and food security in the Rwandese context and argue that "it is less clear if rural food markets are capable of supplying diverse and nutritious foods at affordable prices on a consistent basis, resulting in a lack of diversity and hence, low nutrient quality diets". Erokhin [114] suggests that "trade protectionism challenges the sustainability of food supply by decreasing food availability and quality of food products, causes dietary changes, and threatens the food security of the country", referring to Russia.…”
Section: Markets Food Security and Nutritionmentioning
confidence: 99%
“…Similarly, Huang and Tian [136] argue that enhanced accessibility to food, thanks to the development of market, has improved dietary quality among Chinese people and note that "the impact of food accessibility on dietary quality is stronger for those not engaged in agriculture production" (p. 92). Weatherspoon et al [137] investigate the linkages between food policy, markets and food security in the Rwandese context and argue that "it is less clear if rural food markets are capable of supplying diverse and nutritious foods at affordable prices on a consistent basis, resulting in a lack of diversity and hence, low nutrient quality diets". Erokhin [114] suggests that "trade protectionism challenges the sustainability of food supply by decreasing food availability and quality of food products, causes dietary changes, and threatens the food security of the country", referring to Russia.…”
Section: Markets Food Security and Nutritionmentioning
confidence: 99%
“…Lack of food composition data for locally grown crops is also a challenge in the formulation of nutritious diets. All these are the factors contributing to the high prevalence of malnutrition in Rwanda among under-5 year-old children, where 35% are stunted, 2% wasted and 12.6% underweight [1] mainly due to inadequate complementary food intake and low dietary diversity [2]. There is a need to formulate nutrient-rich shelf stable food products that are convenient and affordable to all.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated NF food for the SSA is higher than that for Rwanda, reflecting how much daily human diets are deficient in proteins. However, there is little progress in Rwanda's diet pattern; with a gentle increase in animal protein consumption, malnutrition is a severe problem in Rwanda (Weatherspoon et al, 2019). The food and nutrition security indicators report showed that about 48.7 and 22.1% of rural and urban populations in Rwanda were still food and nutrition insecure (FAO, 2018).…”
Section: The Nf Food Snmfs and Their Influencesmentioning
confidence: 99%
“…To achieve the daily protein mass advised, we suggest fortifying the consumption of high protein food products, such as animal-derived food products. Moreover, the development of rural food markets and rural nutrition education on reliable consumption of various foods should focus on growing specific nutritive crops rich in protein, micronutrients, and calories (Weatherspoon et al, 2019). Furthermore, farmers' field schools in Rwanda could reinforce farmers' awareness of ecological phenomena affecting their production of crops and animals.…”
Section: The Nf Food Snmfs and Their Influencesmentioning
confidence: 99%